Flux of Particulate Elements in the North Atlantic Ocean Constrained by Multiple Radionuclides. Issue 12 (3rd December 2018) - Hayes, Christopher T.; Black, Erin E.; Anderson, Robert F.; Baskaran, Mark; Buesseler, Ken O.; Charette, Matthew A.; Cheng, Hai; Cochran, J. Kirk; Edwards, R. Lawrence; Fitzgerald, Patrick; Lam, Phoebe J.; Lu, Yanbin; et al.
Abstract: Sinking particles strongly regulate the distribution of reactive chemical substances in the ocean, including particulate organic carbon and other elements (e.g., P, Cd, Mn, Cu, Co, Fe, Al, and 232 Th). Yet, the sinking fluxes of trace elements have not been well described in the global ocean. The U.S. GEOTRACES campaign in the North Atlantic (GA03) offers the first data set in which the sinking flux of carbon and trace elements can be derived using four different radionuclide pairs ( 238 U :234 Th ;210 Pb: 210 Po; 228 Ra: 228 Th; and 234 U: 230 Th) at stations co‐located with sediment trap fluxes for comparison. Particulate organic carbon, particulate P, and particulate Cd fluxes all decrease sharply with depth below the euphotic zone. Particulate Mn, Cu, and Co flux profiles display mixed behavior, some cases reflecting biotic remineralization, and other cases showing increased flux with depth. The latter may be related to either lateral input of lithogenic material or increased scavenging onto particles. Lastly, particulate Fe fluxes resemble fluxes of Al and 232 Th, which all have increasing flux with depth, indicating a dominance of lithogenic flux at depth by resuspended sediment transported laterally to the study site. In comparing flux estimates derived using different isotope pairs, differences result from different timescales of integration and particle size fractionation effects. The range in flux estimates produced by different methods provides a robust constraint on the true removal fluxes, taking into consideration the independent uncertainties associated with each method. These estimates will be valuable targets for biogeochemical modeling and may also offer insight into particle sinking processes. Plain Language Summary: Elements, like iron and carbon, are transported from the ocean's surface to its depths on sinking particles. Access to carbon, iron, and other elements is important for marine organisms, which need them to survive. Furthermore, when the organic carbon produced by organisms is transported to depth by sinking, carbon dioxide has been effectively removed from the atmosphere and moved to the deep ocean. This carbon sink is one way that the ocean reduces the heat‐trapping potential of the atmosphere. To track how much of a given element descends on particles through the ocean, we use radioisotopes. These are elements that decay at a predictable rate. We can use them like a clock to determine how fast an element is moving from one location to another. Radioisotopes with varying decay rates can tell us about short‐term processes, like seasonal blooms, and longer term events, like the impact of ice ages. There were few ocean‐scale radioisotope data sets before GEOTRACES expeditions began about 10 years ago. For the first time ever, we present four types of radioisotope data from the U.S. GEOTRACES expedition across the North Atlantic and discuss how it improves our understanding of elemental budgets in the global ocean. Key Points: North Atlantic flux of particulate carbon and trace elements constrained with four radionuclide methods over the entire water column Fluxes derived from radionuclide methods at BATS are in agreement with sediment trap fluxes C, P, and Cd have biogenic flux profiles; Mn, Co, and Cu have mixed behavior flux profiles; and Fe, Al, and Th‐232 have lithogenic flux profiles